2016
DOI: 10.17265/2159-5828/2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A Field Test of All-Weather Surfaces for Horse Paddocks

Abstract: This field study sought to determine the all-weather surface construction providing the least contaminated runoff and drainage effluent when exposed to moderate to heavy precipitation and different manure loads in horse paddocks during wintertime. Two different combinations of non-woven and woven geotextile together with two gravel fractions of 200 mm were exposed to precipitation and horse manure/urine for two years under two manure regimes (manure removal and manure accumulation). In a simulated rainfall (SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previously, several other authors have also reported that horse paddocks may pose a high risk of extensive P loss [22][23][24][25]55,59]. Regular removal of dung from paddocks is recommended to minimize this risk [25,55,60,61]. How often this should be done naturally depends on the time the horses spend in the paddocks and livestock density/ha.…”
Section: Impact Of Horse Diets On P Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, several other authors have also reported that horse paddocks may pose a high risk of extensive P loss [22][23][24][25]55,59]. Regular removal of dung from paddocks is recommended to minimize this risk [25,55,60,61]. How often this should be done naturally depends on the time the horses spend in the paddocks and livestock density/ha.…”
Section: Impact Of Horse Diets On P Leachingmentioning
confidence: 99%
“…How often this should be done naturally depends on the time the horses spend in the paddocks and livestock density/ha. Phosphorus sorbing materials (e.g., Fe containing) [22,59], filtering materials (geotextile-gravel) [61], or organic (bedding) materials [62] can also be used on paddock surfaces to reduce leaching loss.…”
Section: Impact Of Horse Diets On P Leachingmentioning
confidence: 99%